Editorial - Preudhikulpradab, Sirichai (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
This ABAC ODI Journal issue has 13 articles from research-based works by graduate students, business and organization practitioners, and academia. The contributing authors comprise local and international scholars from Australia, China, Myanmar, the Philippines, Thailand, and USA. This issue also includes the book review: Understanding Power: The Indispensable Chomsky. In terms of types of research, thirteen articles are a combination of quantitative research (5 articles), mixed-method research (5 articles), and qualitative research (3 articles).